The Mystery of Chilaiditi: Air Under the Diaphragm without Perforation - Seballos, Valentina; Salvatierra, Martín (Cirugía del Uruguay, 2025)
Chilaiditi's sign is a rare radiological finding; it corresponds to the interposition of the intestine between the liver and the diaphragm. Generally, this anomaly is asymptomatic, in some cases it can generate symptoms and complications that lead to the diagnosis of "Chilaiditi syndrome." This analysis originated from a clinical case in our department, which prompted a reflection on the importance of an accurate diagnosis.